Tantangan Digitalisasi Program Kewirausahaan Di Lembaga Pendidikan Islam - Rita Juliawati; Niswatun Al-Anah Wibowo; Ajahari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the challenges of digitalizing entrepreneurship programs in Islamic educational institutions and the solutions for their development. This research used a descriptive qualitative approach with the type of library research. Data were obtained from books, journals, scientific articles, and relevant previous studies. The results show that entrepreneurship programs in many Islamic educational institutions are still conventional and have not fully adapted to the development of the digital business world. The main challenges include limited teacher competence, lack of technological facilities, non-integrated curriculum, and the rapid changes in digital business trends. The proposed solutions include curriculum renewal, project-based learning, improving teacher competence, providing supporting facilities, and collaboration with business practitioners. All of these processes need to be based on Islamic values such as honesty, trustworthiness, responsibility, and business ethics. Therefore, the digitalization of entrepreneurship programs becomes an important step in preparing students who are religious, independent, innovative, and ready to face the future.